2020
DOI: 10.1093/mnras/staa1085
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mass-loss rate evolution of stars with ≳18 M⊙ and missing optically observed type II core-collapse supernovae

Abstract: We evolve stellar models with zero age main sequence (ZAMS) mass of M ZAMS 18M ⊙ under the assumption that they experience an enhanced mass-loss rate when crossing the instability strip at high luminosities, and conclude that most of them end as type Ibc supernovae (SNe Ibc) or dust-obscured SNe II. We examine the hydrogen mass in the stellar envelope and the optical depth of the dusty wind at explosion, and crudely estimate that only about a fifth of these stars explode as unobscured SNe II and SNe IIb. About… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…This is roughly consistent with the rate estimate from Eldridge et al (2018) (∼ 4.7%; see §4.3). Recently, Gofman et al (2020) apply enhanced mass-loss rates to RSGs and found that massive RSGs (M ZAMS 20-21 M ) with a similar M Henv range (∼ 0.8-1.8 M ) to that of our short-plateau SN models end up as dustunobscured SNe II. They roughly estimate a rate of this class to be 2-4% of all SNe II, which is similar to our estimate of short-plateau SNe.…”
Section: Implications For the Rsg Problemmentioning
confidence: 54%
“…This is roughly consistent with the rate estimate from Eldridge et al (2018) (∼ 4.7%; see §4.3). Recently, Gofman et al (2020) apply enhanced mass-loss rates to RSGs and found that massive RSGs (M ZAMS 20-21 M ) with a similar M Henv range (∼ 0.8-1.8 M ) to that of our short-plateau SN models end up as dustunobscured SNe II. They roughly estimate a rate of this class to be 2-4% of all SNe II, which is similar to our estimate of short-plateau SNe.…”
Section: Implications For the Rsg Problemmentioning
confidence: 54%
“…Pre-SN outbursts are often observed especially in Type IIn that display narrow emission lines for extended times after the explosion (e.g., Ofek et al 2014) as a consequence of the shock interaction between the slow-moving circumstellar medium (CSM) and the ejected material of the explosion (Smith 2014). However, the underlying physical mechanism that triggers those outbursts and the mass loss rates involved remain elusive (e.g., Beasor et al 2020;Gofman et al 2020;Humphreys et al 2020;Hosseinzadeh et al 2022;Ou et al 2023). Direct identification of progenitors and the environments of stars via preexplosion imaging becomes crucial in understanding these unsolved questions.…”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, the collapse of the core to form a black hole will probably lead to a super-energetic CCSN, i.e., an explosion energy of E exp > 10 52 erg (Gilkis et al 2016). The two explosion mechanisms differ in some of their other predictions (e.g., Gofman et al 2020).…”
Section: Introductionmentioning
confidence: 99%